Financial Literacy and Food Security in Extremely Vulnerable Households - Daniel L. Millimet; Ian K. McDonough; Thomas B. Fomby (Institute for the Study of Labor (IZA), 2015)
Food insecurity is one of the most, if not the most, significant, nutrition-related public health issue confronted in the US. Unfortunately, we know very little about the determinants of food security except that it is not synonymous with poverty. Many households above the poverty line are food insecure; many below are not. We investigate a lack of financial literacy as a potential salient determinant of household-level food security. In light of the recent financial crisis and the burgeoning literature on financial literacy, we know that inadequate financial skills and practices are a significant problem that spans all socioeconomic groups. Using original survey data collected among food pantry clients in North Texas, we assess the causal effect of financial literacy on food security. Our results indicate a strikingly significant effect, both economically and statistically.
Keywords: I12; I18; 330; food security; financial literacy; poverty